PENGARUH RENTABILITAS DAN lIKUIDITAS PADA JUMLAH OPSI SAHAM DAN DAMPAKNYA PADA NILAI PERUSAHAAN - Menawati, Ni Made Wiwik; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The aim of this study was to obtain empirical evidence determine the effect on the profitability and liquidity of the company's value by the number of shares that was announced as an intervening variable. Path analysis is a method used in this study. The results showed that (1) Profitability gave positive effects on the number of shares that was announced (2) Liquidity gave positive effects on the number of shares that was announced, (3) Profitability gave positive influence on the enterprise value of the company (4) Liquidity gave positive effect on the value of the company, (5) the number of shares announced gave positive effects on the value of the company, (6) the profitability did not having any effect on the value of the company through a number of shares was announced, (7) the liquidity had effect on the value of the company through a number of shares was announced.
Keywords: profitability, liquidity, stock options, and the value of the company